The combination of alkaline water provision and asthma-induced gymnastics towards peak expiratory flow rate of asthma patients at Surakarta Lung Clinic, Indonesia - Permadani, Agista Delima; Mardiyono, Mardiyono; Santjaka, Aris (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Asthma is an abnormality in the form of chronic airway inflammation which can be reduced by providing asthma-induced gymnastics and healthy lifestyle such as consuming alkaline water.Aims: The objective of this study is to examine a combination of alkaline water provision and asthma-induced gymnastics towards peak expiratory flow rate of asthma patients at Surakarta Lung Clinic, IndonesiaMethods: This research was a quasi-experimental pre-test-post-test design with control group. The number of respondents in this study was 30 respondents, divided equally into intervention group and control group. The control group was given asthma-induced gymnastics twice a week for 14 days with duration of 60 minutes, while the intervention group was provided with a combination of alkaline water pH9+ for 14 days as much as 1,200 ml/day and asthma-induced gymnastics 4 times a week for 14 days with a duration of 60 minutes.Results: There was a significant difference in the value of peak expiratory flow for 14 days in the intervention group and the control group (p < 0.001). There was an improvement in the average of peak expiratory flow rate values for each measurement in both groups, however, this study orchestrates that the intervention group has a higher improvement than the control group. The combination of alkaline water and asthma-induced gymnastics effectively and significantly improves the peak expiratory flow rate values at the Day 8 (p = 0.039) and the Day 14 (p = 0.012).Conclusion: The combination of alkaline water and asthma-induced gymnastics can be applied in nursing care management in patients with intermittent and persistent asthma. Keywords: Alkaline Water, Asthma Gymnastics, Peak Expiratory Flow Rate, Asthma.